Incest & influence: the private life of bourgeois England - Kuper, Adam (Harvard University Press, 2009)
The romance of incest and the love of cousins -- The law of incest -- The science of incest and heredity -- The family business -- Wilberforce and the Clapham sect -- Difficulties with siblings -- The bourgeois intellectuals -- The Bloomsbury version